LAND SUITABILITY EVALUATION FOR SUGARCANE IN SEGOROMULYO VILLAGE, PAMOTAN SUBDISTRICT, REMBANG REGENCY - Nugroho, Stefanus Feby; Saidi, Didi; Partoyo, Partoyo (Universitas Pembangunan Nasional Veteran Yogayakarta, 2023)
Sugarcane planting in Pamotan Subdistrict, Rembang Regency took place before 2000, but in recent years farmers have complained of declining yields. Data from the Central Statistics Agency for Rembang Regency shows that the productivity of sugarcane in Pamotan Subdistrict in 2011 produced 6,000 kg/ha, 2014 produced 4,597 kg/ha, and 2017 produced 4,200 kg/ha. This study aims to determine the characteristics of the land and land suitability class for sugar cane in Segoromulyo Village. The method used is the matching method, the determination of sample points is carried out using a purposive method based on the land system which is determined from the overlay of soil type maps, slope maps, and land use maps. The parameters measured include average temperature, water availability/rainfall, drainage, texture, coarse material, soil depth, soil CEC, base saturation, pH, C-organic, salinity, erosion hazard, slope, flood/puddle hazard, rock on the surface, and rock outcrops. The results showed that Segoromulyo Village has several land suitability classes for sugar cane, namely S2 with a limiting factor of water availability and oxygen availability of 198.08 ha or around 32.84%, S2 with a limiting factor of water availability, oxygen availability and salinity of 207 .77 ha or around 34.44%, and S3 with a salinity limiting factor of 197.41 ha or around 32.72%.